Stylistic typology of discursive signs in everyday, official and stage communication: an English-Uzbek corpus-acoustic analysis - Kurbanov, Muzaffar Abdumutalibovich (The Lingua Spectrum, 2026)
The article examines stylistic characteristics of discursive signs in everyday, official and stage communication based on English and Uzbek material. The initial focus was vocal evidentiality in English-Uzbek reportage, but the analysis is broadened to verbal-prosodic signs that organize contact, clarification, evidential support, evaluation, deictic anchoring, pause boundaries and politeness mitigation. The corpus contains 2160 annotated units: 720 everyday fragments, 720 official messages and 720 stage utterances. The everyday block also includes a survey of 180 informants. The findings show that everyday communication is marked by contact-transition signs (29.2%), official communication by evidential formulas (30.6%), and stage communication by pause-emphatic concentration (31.3%). Uzbek material has a higher density of evaluative and deictic units, while English material more often uses evidential formulas and politeness mitigators. The proposed model treats the discursive sign as a complex stylistic configuration of language form, intonation and communicative environment.